Lessons of East Asia's economic growth. - HENDERSON, David R. (1997)
Focuses on the economic policies that Washington should encourage in developing countries. Expresses the view that while democracy in no way guarantees economic freedom, economic growth does tend to lead to democracy, and therefore democracy should not be promoted as a solution to poverty. Rather, the best way to promote economic growth and, ultimately, democracy is to encourage governments to free their economies.